Cobrança pelo uso da água: a experiência internacional e brasileira como referenciais para o Estado do Rio Grande do Sul - Godecke, Marcos Vinicius (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Using literature and document research, complemented by interviews and monitoring of public meetings, this study investigates the international and brazilian experience of charging for water use as an economic instrument of management, for its application in the state of Rio Grande do Sul. The literature review showed the regulatory state , the Law 10350/1994, still aligned with best practices and points to aspects to be observed that the application of the instrument induces users to necessary practices for the achievement and maintenance of the water quality and quantity at desired levels.